Revolt! Act I - Benjamin Davidson (EJP import test, 2019)
Summary: A filmed 1972 encounter between Jacques Lacan and a Situationist student occasioned prophetic comments from the analyst about the relationship between revolt, knowledge acquisition and the evolution of communications technology. The historic exchange here serves as the narrative scaffold for a palimpsest in which fragments of found text, italicized throughout, compose a larger fabric assaying the current stakes for psychoanalytic praxis.
Keywords: knowledge; Lacan; Palimpsest; revolt; Sphere